The antiviral role of NF-κB-mediated immune responses and their antagonism by viruses in insects. (5th May 2022) - Cheung, Yin P.; Park, Sohyun; Pagtalunan, Justine; Maringer, Kevin
Abstract : The antiviral role of innate immune responses mediated by the NF-κB family of transcription factors is well established in vertebrates but was for a long time less clear in insects. Insects encode two canonical NF-κB pathways, the Toll and Imd ('immunodeficiency') pathways, which are best characterised for their role in antibacterial and antifungal defence. An increasing body of evidence has also implicated NF-κB-mediated innate immunity in antiviral responses against some, but not all, viruses. Specific pattern recognition receptors (PRRs) and molecular events leading to NF-κB activation by viral pathogen-associated molecular patterns (PAMPs) have been elucidated for a number of viruses and insect species. Particularly interesting are recent findings indicating that the cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) pathway detects viral RNA to activate NF-κB-regulated gene expression. We summarise the literature on virus-NF-κB pathway interactions across the class Insecta, with a focus on the dipterans Drosophila melanogaster and Aedes aegypti . We discuss potential reasons for differences observed between different virus-host combinations, and highlight similarities and differences between cGAS-STING signalling in insects versus vertebrates. Finally, we summarise the increasing number of known molecular mechanisms by which viruses antagonise NF-κB responses, which suggest that NF-κB-mediated immunity exerts strong evolutionary pressures on viruses. These developments in our understanding of insect antiviral immunity have relevance to the large number of insect species that impact on humans through their transmission of human, livestock and plant diseases, exploitation as biotechnology platforms, and role as parasites, pollinators, livestock and pests.